2018
DOI: 10.1007/s10875-018-0512-0
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Influenza in Two Related Adults with Inherited GATA2 Deficiency

Abstract: The pathogenesis of life-threatening influenza A virus (IAV) disease remains elusive, as infection is benign in most individuals. We studied two relatives who died from influenza. We Sanger sequenced GATA2 and evaluated the mutation by gene transfer, measured serum cytokine levels, and analyzed circulating T- and B-cells. Both patients (father and son, P1 and P2) died in 2011 of H1N1pdm IAV infection at the ages of 54 and 31 years, respectively. They had not suffered from severe or moderately severe infections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 49 publications
(107 reference statements)
1
28
0
Order By: Relevance
“…Four IEIs-GATA2 (Bigley et al 2011;Pasquet et al 2013;Sologuren et al 2018), IRF7 (Ciancanelli et al 2015), IRF9 (Hernandez et al 2018), and TLR3 (Lim et al 2019) deficiencies-have been shown to cause life-threatening influenza pneumonitis (Table 1). Autosomal dominant (AD) GATA2 deficiency is the only one of these IEIs leading to a pleiotropic syndromic disorder that manifests as a lack of multilymphoid and granulocyte-macrophage progenitors in the bone marrow, smaller numbers of dendritic cells (DCs), monocytes, T, B and NK lymphocytes in peripheral blood, and higher susceptibility to viral, mycobacterial, and fungal infections.…”
Section: Inherited Gata2 Deficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…Four IEIs-GATA2 (Bigley et al 2011;Pasquet et al 2013;Sologuren et al 2018), IRF7 (Ciancanelli et al 2015), IRF9 (Hernandez et al 2018), and TLR3 (Lim et al 2019) deficiencies-have been shown to cause life-threatening influenza pneumonitis (Table 1). Autosomal dominant (AD) GATA2 deficiency is the only one of these IEIs leading to a pleiotropic syndromic disorder that manifests as a lack of multilymphoid and granulocyte-macrophage progenitors in the bone marrow, smaller numbers of dendritic cells (DCs), monocytes, T, B and NK lymphocytes in peripheral blood, and higher susceptibility to viral, mycobacterial, and fungal infections.…”
Section: Inherited Gata2 Deficiencymentioning
confidence: 99%
“…Autosomal dominant (AD) GATA2 deficiency is the only one of these IEIs leading to a pleiotropic syndromic disorder that manifests as a lack of multilymphoid and granulocyte-macrophage progenitors in the bone marrow, smaller numbers of dendritic cells (DCs), monocytes, T, B and NK lymphocytes in peripheral blood, and higher susceptibility to viral, mycobacterial, and fungal infections. However, the severity of each manifestation varies between patients, and relatives with at-risk genotypes can be asymptomatic (Bigley et al 2011;Pasquet et al 2013;Sologuren et al 2018;Dickinson et al 2011Dickinson et al , 2014Spinner et al 2014;Collin et al 2015;Donadieu et al 2018). The deaths of four adults from severe infections despite the presence of IAV-neutralizing antibodies in the serum have been reported (Bigley et al 2011;Pasquet et al 2013;Sologuren et al 2018).…”
Section: Inherited Gata2 Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, genetic susceptibility to devastating influenza does not appear to be a polygenic trait, but is determined by defects in single genes that govern non-redundant pathways of type I (α/β) and type III (λ) interferon (IFN) responses. Critical genes identified so far are either involved in induction of type I and type III IFNs (TLR3, IRF7) (Ciancanelli et al 2015;Lim et al 2019), IFN production by plasmacytoid dendritic cells (GATA2) (Sologuren et al 2018) or are part of the IFN signaling pathway required for antiviral action (IRF9) . Surprisingly, however, no clear defects have yet been found in type I and type III IFN-stimulated genes (ISGs).…”
Section: Introductionmentioning
confidence: 99%
“…6g), when predicting severe versus moderate influenza. We next compared the performance of RNF144A against those of published genes associated with influenza severity, IFITM3 39 , TLR3 40 , MX1 (in mice) 41 , IRF7 42 , GATA2 43 and CD177 (a neutrophil-specific marker) 38 , as well as CD8A. Only CD177, IFITM3, TLR3 and RNF144A expressions were able to predict influenza severity.…”
Section: Reduced Rnf144a Expression Is Associated With Greater Severimentioning
confidence: 99%